Impact of Digital Trade Barriers on China’s Cross-Border E-commerce Export Performance and Countermeasures - Qiao, Shichao (Journal of Global Economy, Business and Finance, 2026)
Based on the convergence of digital economy and globalization, cross-border e-commerce becomes a new engine driving the high-quality development of China’s foreign trade. However, the emergence and widespread existence of digital trade protectionism have triggered digital trade barriers in many countries, which have seriously restrained the growth of China’s cross-commerce export. Currently, the specific forms, transmission paths and driving mechanisms of digital trade barriers restraining China’s cross-border e-commerce export performance have not been deeply clarified yet, and the current response strategies are still lacking in specificity and systematicness. This study starts from reviewing the related theories and research progresses to find out the research gaps of existing studies, and then constructs the research framework. By employing panel data regression models, mediation effect analysis and case study methods based on data of China’s cross-border e-commerce exports and representative enterprise cases, this study empirically explores the influence and implementation paths of digital trade barriers on export performance, and then proposes corresponding countermeasures from the perspectives of government, industry and enterprise. Empirical findings show that, in terms of specific forms, for every one unit increase in the index of digital trade barriers, the export growth rate decreases by 12 percentage points, and the profit margin decreases by 8 percentage points, which proves that the digital trade protectionist policies have a direct restraining effect on cross-border e-commerce exports. Improving digital infrastructure, enhancing international norms compatibility and strengthening enterprise’s digital capabilities can weaken the dampening effect.